Crosslinked Carbon Dots as Ultra‐Bright Fluorescence Probes. Issue 4 (15th February 2013) - Anilkumar, Parambath; Cao, Li; Yu, Jing‐Jiang; Tackett, Kenneth N.; Wang, Ping; Meziani, Mohammed J.; Sun, Ya‐Ping
Abstract: Carbon dots (surface‐passivated small carbon nanoparticles) are crosslinked to result in fluorescence probes containing one or multiple dots. For the single‐dot probes, the crosslinking further stabilizes the dot structure, while for those packed with multiple dots, the individual probe imaging results demonstrate that the fluorescence properties are additive, with more dots for higher emission intensities in a proportional fashion, thus enabling the preparation of ultra‐bright fluorescence probes. Abstract : Crosslinked carbon dots result in fluorescence probes containing one or multiple dots. For the single‐dot probes, the crosslinking further stabilizes the dot structure, while for those packed with multiple dots, the individual probe imaging results demonstrate that the fluorescence properties are additive, with more dots for higher emission intensities in a proportional fashion, thus enabling the preparation of ultra‐bright fluorescence probes.